A tertiary hospital audit of opioids and sedatives administered in the last 24 h of life. Issue 3 (March 2016) - Douglas, C.; Clarke, M.; Alexander, S.; Khatun, M.
Abstract : Background/Aim: To audit the doses of opioids and sedatives administered to patients in the last 24 h of life in an Australian tertiary hospital and compare results with doses published in New Zealand (NZ) benchmarking studies and to examine the effect of caring for dying patients using a modified version of the Liverpool Care Pathway (mLCP) in respect to doses of opioids and sedatives. Methods: A retrospective chart audit of 102 patients who died in a tertiary hospital was carried out over a 3‐month period in 2011. Diagnosis, demographic patient characteristics, use of the mLCP, use of subcutaneous infusions and key symptoms were identified. Chi‐squared and the non‐parametric Mann–Whitney tests were applied to compare the group differences for categorical and continuous variables as appropriate. Parenteral morphine‐equivalent daily dose (pMEDD) was calculated. A t ‐test assessed the variable mean doses of medication and patient characteristics. Results: Of the audited patients, 76.5% died of non‐malignant disease. The overall mean dose of midazolam was significantly lower compared with that of the NZ study pMEDD (6.0 vs 20.7 mg). The overall mean dose of morphine benchmarked closely with the NZ study (56.5 mg Australian study vs 47.8 mg NZ study). A total of 83% of patients with a malignant diagnosis was supported with the mLCP compared with 51% of patients with a non‐malignant diagnosis. Conclusion: The significance of the lower midazolam doses was postulated, including the possibility of inadequate symptom control for patients with a non‐malignant diagnosis. The use of the mLCP did not lead to the provision of higher doses of medications.